USING FUZZY ANALYTICAL HIERARCHY PROCESS TO PRIORITIZE MEASUREMENT INDICATORS OF EMPLOYEE WELL-BEING IN ORO KOPI GAYO COMPANY - Budi Irwansyah; Yenny Suzana; Subria Mamis; Indriyani Indriyani (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The need to measure complex dimensions of social and humanitarian problems such as quality of life, welfare, and health which cannot be measured using classical techniques, provides an opportunity for the fuzzy logic approach to solve these problems thanks to its ability to work within a framework uncertainty, ambiguity, and unclear information. This research aims to prioritize indicators for measuring employee well-being at the Oro Kopi Gayo company in conditions of uncertainty. Using Chang's Extent Analysis Method in the Fuzzy Analytical Hierarchy Process, this paper evaluates five main components of employee well-being: work satisfaction, organizational respect for the employee, employer care, positive/negative emotions, and intrusion of work into private life. It is hoped that the results of this research can be used as a reference in further research to determine the influence of these five criteria on employee well-being at the Oro Kopi Gayo company